A Framework for Improving Computer-based Information Systems Auditing - Abdirahman, Yusuf Sheikh Khalif (International Journal of Computer (IJC), 2017)
Although Enormous investment is currently being made in computer-based information systems but many of them suffer chronic problems of information security and efficiency [1]. There is a concern about whether the standard quality and security of computer-based information systems is being achieved. As a consequence, growing attention is being paid to evaluating the information systems [2]. The main purpose of this paper was to propose a framework for improving computer-based information systems auditing. The study has two main features; firstly it structures the audit process; secondly it allows the evaluation of computer-based information systems according to a specific set of criteria based on quality, security, compliance and readability requirements. A descriptive survey research design was conducted to gather the primary data. In this paper, the researcher identified shortcomings of some accredited existing IT audit frameworks, and proposed an improved model of audit framework that addresses the main aspect of information security and performance. Therefore, the main purpose of this paper is to come out with a holistic Information System Audit framework that incorporates the general aspects of other important IS audit frameworks that can serve as a guide in Information System Audit for large and medium-sized institutions.